Circadian influence on the microbiome improves heart failure outcomes. (December 2020) - Mistry, Priya; Reitz, Cristine J.; Khatua, Tarak Nath; Rasouli, Mina; Oliphant, Kaitlyn; Young, Martin E.; Allen-Vercoe, Emma; Martino, Tami A.
Abstract: Myocardial infarction (MI) leading to heart failure (HF) is a major cause of death worldwide. Previous studies revealed that the circadian system markedly impacts cardiac repair post-MI, and that light is an important environmental factor modulating the circadian influence over healing. Recent studies suggest that gut physiology also affects the circadian system, but how it contributes to cardiac repair post-MI and in HF is not well understood. To address this question, we first used a murine coronary artery ligation MI model to reveal that an intact gut microbiome is important for cardiac repair. Specifically, gut microbiome disruption impairs normal inflammatory responses in infarcted myocardium, elevates adverse cardiac gene biomarkers, and leads to worse HF outcomes. Conversely, reconstituting the microbiome post-MI in mice with prior gut microbiome disruption improves healing, consistent with the notion that normal gut physiology contributes to cardiac repair. To investigate a role for the circadian system, we initially utilized circadian mutant Clock ∆19/∆19 mice, revealing that a functional circadian mechanism is necessary for gut microbiome benefits on post-MI cardiac repair and HF. Finally, we demonstrate that circadian-mediated gut responses that benefit cardiac repair can be conferred by time-restricted feeding, as wake time feeding of MI mice improves HF outcomes, but these benefits are not observed in MI mice fed during their sleep time. In summary, gut physiology is important for cardiac repair, and the circadian system influences the beneficial gut responses to improve post-MI and HF outcomes. Graphical abstract: Unlabelled Image Highlights: An intact GM benefits cardiac repair post-MI and HF outcomes. GM reconstitution improves healing. A functional circadian mechanism underlies these benefits. Circadian influence conferred by time-restricted feeding. Circadian system influences gut physiology to improve cardiac outcomes. *GM = gut microbiome *MI = myocardial infarction *HF = heart failure